Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1002/humu.22449
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Heart Defects in Patients with Deletions Upstream ofSOX9

Abstract: Heterozygous loss-of-function coding-sequence mutations of the transcription factor SOX9 cause campomelic dysplasia, a rare skeletal dysplasia with congenital bowing of long bones (campomelia), hypoplastic scapulae, a missing pair of ribs, pelvic, and vertebral malformations, clubbed feet, Pierre Robin sequence (PRS), facial dysmorphia, and disorders of sex development. We report here two unrelated families that include patients with isolated PRS, isolated congenital heart defect (CHD), or both anomalies. Pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 19 publications
1
28
0
1
Order By: Relevance
“…These individuals, either XX or XY, were investigated because of Pierre-Robin syndrome or cardiac defects. 11,13,28,29 The two duplications that we described are both in tandem, as reported for other DSD cases, 4,5 but a specific predisposing genomic architecture has not been highlighted. This duplication, although without effect in the XY background, appears to be very rare, with no cases containing at least the minimal duplicated RevSex region among the 14 316 individuals collected in the Database of Genomic Variants.…”
Section: Discussionsupporting
confidence: 68%
“…These individuals, either XX or XY, were investigated because of Pierre-Robin syndrome or cardiac defects. 11,13,28,29 The two duplications that we described are both in tandem, as reported for other DSD cases, 4,5 but a specific predisposing genomic architecture has not been highlighted. This duplication, although without effect in the XY background, appears to be very rare, with no cases containing at least the minimal duplicated RevSex region among the 14 316 individuals collected in the Database of Genomic Variants.…”
Section: Discussionsupporting
confidence: 68%
“…We also previously showed that deletions upstream of SOX9 containing regulatory elements are likely responsible for isolated CHD. 24 We performed here a computational approach to search for an enrichment of binding sites of transcription factor genes within our rare CNVs data set that might have altered the expression of genes and thus contributed to the CHD. Our TFBS approach led us to identify a significant enrichment of FOXC1-binding sites in the rare CNVs present in affected children (Table V in the Data Supplement).…”
Section: Discussionmentioning
confidence: 99%
“…Mutations both upstream and downstream of the SOX9 gene have been associated with isolated cases of PRS and it is proposed that these mutations lie in SOX9 enhancers and are required for appropriate SOX9 expression during development [11]. Recently a large 1Mb-sized deletion upstream of SOX9 was found in patients with either isolated PRS, isolated congenital heart defect (CHD), or both of these defects from two families [12]. This large deletion includes enhancers that regulate NKX2.5 and GATA4, genes known to be associated with CHD [42, 43].…”
Section: Introductionmentioning
confidence: 99%